Structural in-situ interventions for the recovery of stream functional aspects: an approach under different hydrological conditions - Bega, João Miguel Merces (2024)
Restoring impacted streams can help recovering or maintaining the ecosystem services associated with the cycling and transformation of matter. However, there is currently a limited number of studies focusing on the evaluation of how stream functional indicators respond to structural in-situ interventions for stream restoration, especially in tropical regions and under stormflow conditions. This research aimed to analyze the effects of implementing cross-vanes and riffles on water quality and functional aspects [metabolic rates and ammonium and soluble reactive phosphorus (SRP) uptake] of a tropical stream in the urban area of São Carlos (SP, Brazil) under two contrasting hydrological conditions: baseflow and stormflow. For this purpose, post-restoration values were compared with pre-restoration measurements and reference conditions reported for streams with minimal anthropogenic impacts in the studied area. Additionally, it sought to elucidate the effects of dam removal (reference, restored, and impacted reaches) on carbon processing in a temperate stream in Sant Sadurní d\'Osormort (Barcelona, Spain), assessing key ecosystem functions (organic matter decomposition, metabolic rates, and gaseous carbon fluxes) across different seasons under baseflow conditions. For the tropical stream, under baseflow conditions, metabolic rates and ammonium and SRP uptake metrics were not completely recovered after the additions. Nevertheless, the interventions altered important in-stream hydromorphological characteristics, with further improvements anticipated in the long-term. Moreover, under stormflow conditions, this research demonstrated that cross-vanes and riffles have limited efficacy in mitigating nonpoint source pollution, at least in urban areas. These structures can temporarily trap sediments and prevent the occurrence of the first flush, but they are not effective in reducing the downstream export of suspended solids and dissolved nutrients within the drainage system as similar or higher (but never lower) event mean concentrations were obtained after restoration. Regarding the temperate stream, organic matter decomposition, metabolic rates, and gaseous carbon fluxes were not completely recovered after dam removal as well. In addition, significant differences in ecosystem functions among stream reaches within seasons were obtained, likely due to uneven variations in hydromorphological and physicochemical characteristics. In both tropical and temperate streams, the ecosystem functions evaluated were mostly linked to changes in hydromorphological characteristics induced by the interventions. Therefore, these functions were confirmed as effective indicators of ecosystem performance in response to stream restoration. The interventions applied in this research align with the Sustainable Development Goals (SDGs), specifically Goal 6 (clean water and sanitation for all) and Goal 14 (life below water). By elucidating the effects of these techniques under varying hydrological conditions, the findings of this study can inform the development of criteria and methodologies for future environmental restoration projects of impacted streams under climate change scenarios, contributing to the achievement of the aforementioned SDGs.